The effects of massage on delayed onset muscle soreness and physical performance in female collegiate athletes - Mancinelli, C. A.; Davis, D. S.; Aboulhosn, L.; Brady, M.; Eisenhofer, J.; Foutty, S. (Physical Therapy in Sport, 2006)
Objective: The purpose of this study was to determine if post-exercise massage has an effect on delayed-onset muscle soreness (DOMS) and physical performance in women collegiate athletes. Design: This study used a randomized pre-test post-test control group design. Participants: Twenty-two NCAA Division I women basketball and volleyball players participated. On the day of predicted peak soreness, the treatment group (n = 11) received a thigh massage using effleurage, petrissage and vibration while the control group (n = 11) rested. Outcome measures: Paired t-tests were used to assess differences between pre and post massage measures (a=0.05) for vertical jump displacement, timed shuttle run, quadriceps length and pressure-pain threshold in the thigh. Results: A significant increase (slowing) was found in shuttle run times for the control group (p =0.0354). There were significant changes in vertical jump displacement (p = 0.0033), perceived soreness (p = 0.001 1) and algometer readings (p = 0.0461) for the massage group. Conclusions: This study supports the use of massage in women collegiate athletes for decreasing soreness and improving vertical jump.